Qualidades intrínsecas para inovação de produtos em piso e revestimento de cerâmica vermelha do APL de São Miguel do Guamá - MENDES, Adriana de Nazaré Moraes Mendes de (Universidade Federal do Pará, 2013)
This dissertation represents a contribution in solving the problem of innovation of products in the red ceramic industry in São Miguel do Guamá, state of Pará. It is a methodology, based on the strategy of QFD (Quality Function Deployment) which combines the requirements of consumers in the preparation of the product designs and production processes. The lack of knowledge of products or services to be sold is a major (and obvious) reasons for the failure of small retailers and services. In the current level of competitiveness, information is the key to business success and adapt to the market, not only to obtain and collect this information, but also to learn to interpret them and use them properly and in a creative way. The product quality is assessed both in terms of internal (technical) and the external aspect (quality required by customers). Research shows, in addition to the living reality of the industry of ceramics industries, the importance and attributes of quality defined by consumers on the red tiles. The work also shows the application of a methodology for companies in the sector through unfolding of the required quality, the quality is down planned.